Pro Access 2007 - Reid, Martin W P.; SpringerLink (Online service) (Berkeley, CA : Apress, 2007)
Pro Access 2007 covers the features of Microsoft Access 2007, including working with SharePoint Office Server and customizing Ribbons. The book is aimed at professional developers and power users who are new to Access 2007. Among other topics, youll learn about the new Access menu structure, including customization, as well as new SharePoint features. This book provides good, short, solid information with as little waffle as possible. And the book includes solid examples that thoroughly explain new features. Author Martin Reid is also a working Access developer who is respected by his peers and knows what working developers face, especially at the time of a new release.
Access 2007: What$1 (Bs New? -- Text and Templates -- Getting Up and Running with RibbonX -- Data Collection Using Microsoft Outlook 2007 -- to Classes in VBA -- RAD Development for SQL Server 2000/2005 Express -- Working with the SQL Server 2005 Express Tool Set -- DAO, Complex Data Types, and Macros -- to SharePoint Server -- Access and SharePoint Applications -- Access, SharePoint, and SharePoint Designer -- Getting Started with. NET Tools -- Code You Can Steal!.s
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books